2019
DOI: 10.1155/2019/9596810
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals from Smoked Corbicula fluminea Collected on Roadside Vendors at Kelantan, Malaysia

Abstract: Corbicula fluminea serves as traditional food to the local people in Kelantan, Malaysia. Concerns regarding river contamination, smoking method, and associated adverse effects on public health had been increasing. Hence, this study aims to measure the level of heavy metals (Cd, Cu, Mn, Pb, and Zn) and assess human health risk in C. fluminea consumption at Kelantan. Heavy-metal analysis was done using flame atomic absorption spectrophotometry, while human health risk was assessed using provisional tolerable wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
4
0
2
Order By: Relevance
“…The THQ of the present study were also in tandem with values reported by Moslen and Miebaka [32]. Dee et al [33] also found THQ for Cd, Cu, Mn, Pb, and Zn as 0.12, 0.06, 0.04, 0.41, and 0.03, respectively. The values of hazard quotient carcinogenic (HQ ) of the present study ranged from 10 −6 -10 −4 (Figure 5).…”
Section: Target Hazard Quotientsupporting
confidence: 91%
“…The THQ of the present study were also in tandem with values reported by Moslen and Miebaka [32]. Dee et al [33] also found THQ for Cd, Cu, Mn, Pb, and Zn as 0.12, 0.06, 0.04, 0.41, and 0.03, respectively. The values of hazard quotient carcinogenic (HQ ) of the present study ranged from 10 −6 -10 −4 (Figure 5).…”
Section: Target Hazard Quotientsupporting
confidence: 91%
“…If the HI value of any heavy metals in herbal preparations is less than 1, it implies that the exposed population is unlikely to experience any adverse health effect in their lifetime. However, if the HQ is equal to or higher than 1, there is a potential health risk to the exposed population [22,35,36].…”
Section: Health Risk Assessment Of Heavy Metalsmentioning
confidence: 99%
“…To evaluate the potential hazards resulting from the consumption of food containing Hg, the concept of an estimated daily intake (EDI) and estimated weekly intake (EWI) is commonly used [ 41 , 42 ]. Information on the amount of fish sauce consumed in the world is difficult to find; however, for the Asia–Pacific region, fish sauce consumption is reported as the highest, with a consumption of 4 kg per year per capita reported.…”
Section: Resultsmentioning
confidence: 99%